Decision Support System by using Multiple Attribute Decision making with Simple Additive Weighting Method (Madm-Saw) Method in Selecting the Best Bromelain - Ririn Fatma Nanda; Anwar Kasim; Rini Rini; Daimon Syukri; Muhammad Arwani (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
Bromelain is a protease enzyme obtained from pineapple. In choosing bromelain only pay attention to its chemical analysis and there is no rank yet. Therefore, research has been carried out in making the best bromelain decision using the Multiple Attribute Decision Making with Simple Additive Weighting Method (MADM-SAW) method based on the shelf life of pineapples. The basic concept of this method is to find the weighted sum of the performance branches for each alternative (treatment) of all attributes so that the best alternative will be obtained in the selection of crude bromelain enzymes based on pineapple storage. The results showed that the best pineapple fruit was with storage of day 0 as rank 1, with a total value was 0.9025.